Low consumption BVA resonators - VALENTIN, J.-P. (Archives of Acoustics, 1991)
In this paper the author studies several possibilities to reach low consumption of electrical power in the maintaining of BVA resonator at its turnover. Heatings by dielectric losses, by deposited resistors, by infrared radiations and by acoustic losses are examined. The results of calculations and experiments are presented and discussed. Two solutions are rejected because no convenient for low consumption or for weak aging. The retained solutions could open a new way for manufacturing of minature ovenized resonators.